2021
DOI: 10.1155/2021/5513008
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Radiological Findings in Patients with Newly Diagnosed Graves’ Ophthalmopathy

Abstract: Background. Graves’ ophthalmopathy is the most common extrathyroidal manifestation of Graves’ disease. The objective of this study was to investigate the clinical ophthalmological and MRI findings in newly diagnosed Graves’ ophthalmopathy. Methods. This study included 36 newly diagnosed Graves’ disease patients and 23 control participants. Patients and control participants underwent detailed ophthalmologic examination. In addition, all subjects underwent orbital MRI examination; and sizes, cross-sectional area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Studies seeking to evaluate diagnostic methods and disease grading would better consider disease stage to evidence which method is more sensitive for each distinct stage, as shown by Chen et al. ( 65 69 ). In this MRI study, all findings suggested that the methods used can help to identify the disease activity and staging, providing a better perspective on treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…Studies seeking to evaluate diagnostic methods and disease grading would better consider disease stage to evidence which method is more sensitive for each distinct stage, as shown by Chen et al. ( 65 69 ). In this MRI study, all findings suggested that the methods used can help to identify the disease activity and staging, providing a better perspective on treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…The arrow shows the length from the foremost part of the cornea to the orbital apex on axial T1WI sequence. Reproduced with permission from Cevik et al 12 Copyright 2021 International Journal of Endocrinology. ( b ) Quantitative measurement of EOMs diameters on T1WI for TED diagnosis.…”
Section: Different Quantitative Mri Techniques Utilized In Tedmentioning
confidence: 99%
“…Arrow a shows long diameter and arrow b shows short diameter on coronal T1WI sequence. Reproduced with permission from Cevik et al 12 Copyright 2021 International Journal of Endocrinology. ( c , d ) The patient with active TED had prominent T1CE hyperintensity of EOMs (medial, superior and inferior recti muscles) than the patient with inactive TED.…”
Section: Different Quantitative Mri Techniques Utilized In Tedmentioning
confidence: 99%
“…For this, the axial slice that most obviously depicts the EOMs and optic nerve is selected, and from which the perpendicular distance between the interzygomatic line and the surface of the cornea is measured (Figure 3A) (52). However, depending on the selection of either the anterior or the posterior corneal surface, there can be a difference of 1-2 mm for the exophthalmos determined by MRI and by Hertel ophthalmometry (15,16). In summary, in the absence of guidance from an experienced ophthalmologist, m e a s u r i n g e x o p h t h a l m o s w i t h M R I i s a g o o d diagnostic option.…”
Section: Exophthalmosmentioning
confidence: 99%